WIF1 Qualitative-Methylation from Peripheral Blood Could Not Be Used as Biomarker for The Risk of Nasopharyngeal Carcinoma or Smoking Behavior in Yogyakarta Panel - Aditya Kurniawan; Erika Diana Risanti; Saihas Suhda; Hanggoro Tri Rinonce; Ery Kus Dwianingsih; Jajah Fachiroh (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Tobacco smoking plays an important role in nasopharyngeal carcinoma (NPC) risk. The Wingless-related integration site (WNT) Inhibitory Factor 1 (WIF1) as one of the tumor suppressor gene (TSG), functions to control cell proliferation through suppression of WNT signaling pathway. WIF1 methylation is one of epigenetic mechanisms which causes overactivated of WNT pathway in NPC development. WIF1 methylation from buffy coat related to smoking status and NPC risk is not known yet.METHODS: This was a nested case-control study involving 39 newly diagnosed NPC patients and 40 healthy controls. All subjects were enrolled at Dr. Sardjito Hospital, Yogyakarta. Subjects were male, with known smoking status, duration, and quantity of cigarette consumed. Parallel DNA isolated from buffy coat was used for WIF1 DNA methylation analysis, by using methylation-specific PCR (MSP) method. Chi-square analysis was used to determine distribution of differences among groups. Two tailed p-value≤0.05 was considered as statistically significant.RESULTS: No significant difference between WIF1 methylation of cases and controls (p=0.30), nor smoking habit among smokers (p=0.51) and non-smokers (p=0.43).CONCLUSION: WIF1 methylation from buffy coat could not be used as an NPC marker nor as a smoking behavior marker.KEYWORDS: buffy coat, cigarette smoking, methylation, nasopharyngeal carcinoma, WIF1